Relationship of Implementation Organizational Strategies and Reward Systems with Performance of Employees at Health Center in Konawe Selatan District - Sada, La; Sunarsih, Sunarsih; Kamalia, La Ode (Waluya The International Science of Health Journal, 2022)
Introduction: Organizational functions that include organizational strategy and reward systems have not been fully carried out to the fullest. Based on the preliminary survey, information was obtained that the planning and functions of the organization were not yet fully operational. The purpose of this research is to analyze the relationship between organizational strategy and reward system with employee performance at the Health Center in Konawe Selatan Regency. Method: Quantitative research with approachcross sectional study. The population is all Health Center employees in South Konawe Regency as many as 774 people. The sampling technique used is simple random sampling with a total sample of 86 respondents. Result: The results of the statistical test of organizational strategy using the Chi Square test at = 5% and df = 1, obtained the value of X2 arithmetic > X2 table (8.713> 3.841) and the value of namely 0.318, meaning that there is a significant weak relationship between organizational strategy and employee performance. The reward system at = 5 % and df = 1, obtained the value of X2 count > X2 table (36,203> 3,841) and the value of namely 0.649, there is a strong relationship between the reward system and employee performance. Conclusion: There is a weak relationship between organizational strategy and a strong relationship with employee performance at the Health Center in Konawe Selatan District.